Camilan fungsional sus khi-yam: uji organoleptik dan kimia produk sus kering kacang hijau dan bayam untuk pencegahan anemia - Jairani, Eka Nenni; Fatahillah , Sudana; Sari , Dini Novita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Background: Anemia is when the hemoglobin levels in the blood are lower than the normal range. Anemia can be prevented by consuming foods that are high in protein, iron, and vitamin C. Mung beans (Vigna Radiata) and green spinach (Amaranthus hybridus L.) are foods rich in iron and vitamin C so that they can help hemoglobin formation. Dry Eclairs is a snack enjoyed by all age groups. Adding mung bean flour and spinach flour to prepare dry eclairs aims to make it a healthy snack to prevent anemia. Objectives: The research seeks to determine the organoleptic and chemical test results of dried éclair with mung beans and spinach (Sus Khi-Yam). Methods: The research method used a completely randomized design (CRD) experiment with three treatments (F1, F2, and F3) and two repetitions, resulting in 6 experimental units. The Organoleptic test was conducted with 40 untrained panelists. The Chemical analysis was carried out to determine the levels of iron, antioxidants, vitamin C, fiber, and ash. Results: The organoleptic test showed that the most preferred color by the panelists was in treatment F1, with a preference level of 3.55. For flavor, treatment F2 was the most preferred by the panelists, with a preference level of 3.40. The most preferred taste was also found in the F2 treatment, with a score of 3.50. Meanwhile, the texture of the three treatments did not show significant differences in panelist preference. The Chemical test indicated that the F2 treatment had higher fiber, iron, and antioxidant content than other treatments. Conclusion: Panelist acceptance of Sus Khi-Yam snacks for all treatments (F1, F2, and F3) is acceptable, but the best Sus Khi-Yam snacks according to panelists in terms of color are in F1 treatment, the best Sus Khi-Yam snacks according to panelists in terms of texture are in F3 treatment and the best Sus Khi-Yam snacks according to panelists in terms of taste and aroma are in F2 treatment.